Covid-19, unemployment, and health: time for deeper solutions?. (8th October 2020) - Hensher, Martin
Abstract : As covid-19 drives unemployment rates around the world to levels unseen in generations, once radical economic policy proposals are rapidly gaining a hearing. Martin Hensher examines how job guarantee or universal basic income schemes might support better health and better economics